Lithium metal composite negative electrode and preparation method and application thereof

By constructing a composite layer of polymer and lithium alloy in the negative electrode of the lithium metal battery, the problems of poor interface stability and large internal resistance in the prior art are solved, and high energy density and long-term stable cycle of the lithium metal battery are achieved.

CN119673963AActive Publication Date: 2025-03-21JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411840161.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The interaction between the polymer substrate and the copper layer in the existing composite liquid is weak, resulting in poor structural stability and large internal resistance, which limits the reversibility and kinetics of the lithium metal deposition-stripping process, and is prone to lithium dendrites at the interface between the negative electrode and the separator, affecting the safety and cycle life of the battery.

Method used

By constructing a composite layer containing polymer and lithium alloy between the polymer base layer and the lithium metal layer, interface stability is improved and internal resistance is reduced, thereby improving the reversibility and kinetics of lithium metal in the negative electrode deposition-stripping process. At the same time, the distribution of lithium content in the composite layer is controlled to form a conductive and lithium-philic double gradient, and the lithium nucleation trend is regulated to inhibit the formation of lithium dendrites.

Benefits of technology

The interface stability and internal resistance performance of lithium metal composite negative electrodes are significantly improved, the reversibility and kinetics of lithium metal in the negative electrode deposition-stripping process are enhanced, the cycle life of lithium metal batteries is extended, and the long-term stable cycle is maintained at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673963A_ABST
    Figure CN119673963A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium metal composite negative electrode and a preparation method and application thereof.The lithium metal composite negative electrode comprises a polymer substrate layer, a composite layer and a lithium metal layer which are sequentially arranged from inside to outside, the composite layer comprises a second polymer and lithium alloy, the lithium alloy is LiMx, and M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg and Mn. The lithium metal composite negative electrode can be prepared through simple melting, tape casting and hot rolling, and is suitable for industrial production; the lithium metal composite negative electrode prepared by the preparation method has a conductive and lithium-loving double-gradient composite layer, and lithium deposition at the interface of the negative electrode and a diaphragm can be effectively inhibited. When the lithium metal composite negative electrode is used in the lithium metal battery, the energy density of the battery can be improved, the problem of negative electrode lithium dendrites can be effectively inhibited, and the long-acting stable circulation of the high-energy-density lithium battery can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium metal composite negative electrode and a preparation method and application thereof. Background Art

[0002] Copper foil is one of the materials commonly used in the negative electrode current collector of lithium metal batteries. As an inactive component, copper foil accounts for ~20% of the total mass of lithium batteries, but does not contribute to any capacity. Therefore, replacing traditional copper foil with lightweight components is expected to significantly improve the energy density of lithium batteries. For example, sputtering an ultra-thin copper layer on a polymer substrate as a composite current collector can effectively reduce weight and thus improve the energy density of lithium batteries.

[0003] However, the interaction between the polymer substrate and the copper layer in the existing composite current collector is usually weak, and the copper layer and the polymer substrate are easily separated, resulting in extremely poor structural stability and large internal resistance of the composite current collector, which limits the reversibility and kinetics of the lithium metal deposition-stripping process. In addition, the lithium metal negative electrode prepared by this type of composite current collector is prone to produce lithium dendrites at the interface between the negative electrode and the separator, which seriously affects the safety and cycle life of the battery, and restricts the performance improvement and rapid iteration of lithium batteries. Summary of the invention

[0004] In order to solve the problems of poor interface stability and easy formation of lithium dendrites at the interface between the negative electrode and the diaphragm of the lithium metal negative electrode currently prepared by using traditional composite current collectors, the present invention provides a lithium metal composite negative electrode and its preparation method and application. By constructing a composite layer including a polymer and a lithium alloy between a polymer base layer and a lithium metal layer, the interface stability of the negative electrode can be effectively improved and the internal resistance of the negative electrode can be reduced, thereby improving the reversibility and kinetics of the lithium metal deposition-stripping process in the negative electrode; the present invention further controls the distribution of lithium content in the composite layer so that the composite layer has a conductive and lithium-philic dual gradient, so as to regulate the lithium nucleation trend of the composite layer (at the interface with the polymer base layer) to be better than that of the lithium metal layer surface, thereby effectively inhibiting lithium deposition at the interface between the negative electrode and the diaphragm, so that the lithium metal battery containing the lithium metal composite negative electrode has a high energy density and can be long-term and stably cycled at a high rate.

[0005] Specifically, the following technical solutions are provided:

[0006] A first aspect of the present invention provides a lithium metal composite negative electrode, the lithium metal composite negative electrode comprising a polymer substrate layer, a composite layer and a lithium metal layer;

[0007] The polymer base layer comprises a first polymer;

[0008] The composite layer is disposed on at least one side of the polymer base layer along the thickness direction, and the composite layer comprises a second polymer and a lithium alloy, wherein the lithium alloy is LiM x, wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn, and x is 0.01-2;

[0009] The lithium metal layer is arranged on a side of the composite layer away from the polymer substrate layer.

[0010] Furthermore, in the composite layer, the lithium alloy has a three-dimensional network structure and is in interactive contact with the second polymer.

[0011] Furthermore, the lithium content in the lithium metal composite negative electrode gradually decreases along a first direction, and the first direction is the direction in which the lithium metal layer points to the polymer base layer; more preferably, the lithium content in the composite layer accounts for 25%-75%, for example, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc., including but not limited to the content percentages listed above.

[0012] Furthermore, the first polymer may be selected from one or more of polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyimide (PI), polyamide (PA), and polytetrafluoroethylene (PTFE); the second polymer may be selected from one or more of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polyamide, and polytetrafluoroethylene; more preferably, the first polymer and the second polymer are the same polymer.

[0013] Furthermore, the thickness of the first polymer substrate layer is preferably 4-8 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc., including but not limited to the thicknesses listed above.

[0014] Furthermore, the thickness of the composite layer is preferably 0.5-5 μm, for example 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., including but not limited to the thicknesses listed above.

[0015] Furthermore, the thickness of the lithium metal layer is preferably 0.1-15 μm, for example 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc., including but not limited to the layer thicknesses listed above.

[0016] The second aspect of the present invention provides a method for preparing the lithium metal composite negative electrode according to the first aspect, comprising the following steps:

[0017] S1, providing material A, wherein material A comprises a first polymer, and material B comprises a second polymer and an M source;

[0018] S2, melting material A and material B to form melt A and melt B respectively, and stacking them in an AB or BAB arrangement, and forming a composite film layer by casting; the composite film layer includes an A film layer and a B film layer;

[0019] S3, covering the surface of the composite film layer where the B film layer is located with a lithium metal strip, and performing a roller pressing process to obtain the lithium metal composite negative electrode.

[0020] Furthermore, in step S1, the M source is M element and / or M oxide, wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn.

[0021] Furthermore, in step S1, the M source is in the form of one or more of nanoparticles, nanowires, and nanofibers; more preferably, the particle size of the nanoparticles is 5-1000 nm, and the cross-sectional diameters of the nanowires and nanofibers are 5-100 nm.

[0022] Furthermore, in step S1, the mass proportion of the second polymer in the material B is 1%-30%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc., including but not limited to the mass proportions listed above.

[0023] Furthermore, in step S2, the melt A and the melt B are extruded through dies arranged in a certain arrangement so that the melts are stacked in an AB or BAB arrangement.

[0024] Further, in step S2, the thickness of the A film layer is preferably 4-8 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc., including but not limited to the layer thicknesses listed above.

[0025] Further, in step S2, the thickness of the B film layer is preferably 0.5-5 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., including but not limited to the layer thicknesses listed above.

[0026] Further, in step S3, the thickness of the lithium metal strip is preferably 5-20 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., including but not limited to the layer thicknesses listed above.

[0027] Furthermore, in step S3, the lithium metal tape is coated on the surface of the composite film layer where the B film layer is located by transfer printing.

[0028] Furthermore, in step S3, the rolling pressure is preferably 0.1-100 MPa, and the temperature is preferably 25-100°C.

[0029] A third aspect of the present invention provides a lithium metal battery, comprising a negative electrode plate, wherein the negative electrode plate is the lithium metal composite negative electrode described in the first aspect or the lithium metal composite negative electrode prepared by the preparation method described in the second aspect.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention uses a polymer layer as a matrix, a composite layer containing a polymer and a lithium alloy as a conductive current collector, and the lithium alloy in the composite layer and a lithium metal layer arranged on the side of the composite layer away from the matrix are used together as negative electrode active materials to form an integrated lithium metal composite negative electrode. The integrated lithium metal composite negative electrode is light in weight and can effectively improve the energy density. The composite layer containing a polymer and a lithium alloy has a strong interaction force with the polymer base layer and the lithium metal layer, and has good interface stability and low internal resistance. It can effectively improve the reversibility and kinetics of the deposition-stripping process of lithium metal in the negative electrode, and reduce the phenomenon of uneven lithium deposition on the lithium metal negative electrode; in addition, lithium ions will preferentially deposit on uniformly dispersed conductive lithium-philic lithium alloy sites at the beginning of battery charging, thereby forming uniformly distributed lithium nucleation points. In the process of continuing charging, lithium ions will be uniformly deposited based on these uniform nucleation points, thereby further inhibiting the formation of lithium dendrites and improving the safety and cycle life of the battery.

[0032] 2. The present invention controls the distribution of lithium content in the composite layer in the lithium metal composite negative electrode so that the lithium content in the lithium metal composite negative electrode gradually decreases along the direction from the lithium metal layer to the polymer base layer, thereby forming a conductive and lithium-philic dual gradient (along the direction from the lithium metal layer to the polymer base layer, the lithium-philicity gradually increases and the conductivity gradually decreases). The conductive gradient regulates the lithium nucleation tendency on the surface of the lithium metal layer to be inferior to that at the bottom of the composite layer (at the interface with the polymer base layer), and the lithium-philic gradient regulates the lithium nucleation tendency at the bottom of the composite layer to be superior to that on the surface of the lithium metal layer. Under the synergistic effect of the above-mentioned dual gradient structure, the lithium nucleation tendency at the bottom of the composite layer is much better than that on the surface of the lithium metal layer, thereby effectively inhibiting lithium deposition at the interface between the negative electrode and the diaphragm, and greatly reducing the risk of short circuit in lithium metal batteries.

[0033] 3. The present invention also provides a method for preparing the above-mentioned lithium metal composite negative electrode. By melting, casting and rolling, a lithium metal composite negative electrode with a polymer base layer, a composite layer and a lithium metal layer tightly combined can be obtained. The preparation method has a simple process, low cost, is easy to realize industrial production, and has strong adaptability and universality; and the prepared lithium metal composite negative electrode has a stable structure and can effectively inhibit the formation of lithium dendrites. Specifically as follows: The present invention uses the lithium metal element to diffuse into the composite layer under rolling conditions and react with the M source uniformly dispersed in the B film layer to form a lithium alloy with a three-dimensional structure and a conductive and lithium-philic dual gradient in situ. The lithium alloy with a three-dimensional network structure forms an interactive contact with the polymer in the composite layer, which is beneficial to improve the interface compatibility and adhesion between the polymer and the conductive and lithium-philic dual gradient lithium alloy, and can effectively deal with the volume, internal stress and electrode structure changes caused by the charge and discharge cycle of the lithium metal battery, which is beneficial to improve the coulomb efficiency and cycle life of the battery; and the lithium alloy with a three-dimensional structure can further reduce the internal resistance of the negative electrode and improve the rate performance of the battery. In summary, the lithium metal composite anode prepared by the above method is conducive to achieving long-term stable cycling of high energy density lithium metal batteries at high rates.

[0034] 4. The lithium metal battery composed of the lithium metal composite negative electrode and the high-nickel ternary positive electrode provided by the present invention has a capacity retention rate of not less than 90% after 1000 cycles of charge and discharge, and the capacity retention rate of the battery is still not less than 85% after 1750 cycles of charge and discharge, which is much better than the cycle life of the lithium metal battery assembled with the lithium metal composite negative electrode prepared with the traditional composite copper foil as the current collector under the same conditions (the battery capacity retention rate is only 22.3% after 500 cycles of charge and discharge). BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the structure of the lithium metal composite negative electrode provided by the present invention;

[0036] Figure 2 The cycle performance diagram of a lithium metal battery formed by assembling a high-nickel ternary positive electrode and a lithium metal composite negative electrode prepared in Example 1;

[0037] Icon: 1 is the polymer base layer, 2 is the composite layer, and 3 is the lithium metal layer. DETAILED DESCRIPTION

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."

[0039] As described in the background technology, the use of a lightweight composite current collector as the negative electrode current collector of a lithium metal battery is beneficial to improving the energy density of the lithium battery. However, the existing composite current collector (polymer substrate + copper layer) has poor structural stability and large internal resistance. In addition, the negative electrode using the composite current collector is prone to produce lithium dendrites at the interface between the negative electrode and the diaphragm during the battery charging and discharging process, which seriously affects the safety and cycle life of the battery.

[0040] To solve the above problems, the present invention provides a lithium metal composite negative electrode, such as Figure 1 As shown, the lithium metal composite negative electrode comprises a polymer substrate layer 1, a composite layer 2 and a lithium metal layer 3; the polymer substrate layer 1 comprises a first polymer; the composite layer 2 is arranged on at least one side of the polymer substrate layer 1 along the thickness direction, and the composite layer 2 comprises a second polymer and a lithium alloy, and the lithium alloy is LiM x , wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn, and x is 0.01-2; the lithium metal layer 3 is arranged on the side of the composite layer 2 away from the polymer base layer 1.

[0041] In order to solve the problems that the current composite current collector has poor structural stability, large internal resistance and is easy to generate lithium dendrites at the interface between the negative electrode and the diaphragm when used for the negative electrode, the present invention uses a polymer layer as a matrix, a composite layer including a polymer and a lithium alloy as a conductive current collector, and the lithium alloy in the composite layer and a lithium metal layer arranged on the side of the composite layer away from the polymer substrate are used together as negative electrode active materials to form an integrated lithium metal composite negative electrode. The integrated lithium metal composite negative electrode is light in weight and can effectively improve the energy density, and the composite layer including the polymer and the lithium alloy has a strong interaction force with the polymer substrate layer and the lithium metal layer, has good interface stability and low internal resistance, can effectively improve the reversibility and kinetics of the deposition-stripping process of lithium metal in the negative electrode, and reduce the phenomenon of uneven lithium deposition on the lithium metal negative electrode; in addition, lithium ions will preferentially deposit on the uniformly dispersed conductive lithium-philic lithium alloy sites at the beginning of battery charging, thereby forming uniformly distributed lithium nucleation points, and in the process of continuing charging, lithium ions will be uniformly deposited based on these uniform nucleation points, thereby further inhibiting the formation of lithium dendrites and improving the safety and cycle life of the battery.

[0042] In the present invention, the lithium alloy forms a three-dimensional network structure in the composite layer and interacts with the second polymer in the composite layer, which is beneficial to improving the interface compatibility and adhesion between the second polymer and the conductive, lithium-philic dual-gradient lithium alloy, and can effectively cope with the volume, internal stress and electrode structure changes caused by the charge and discharge cycle of the lithium metal battery, which is beneficial to improving the coulombic efficiency and cycle life of the battery; in addition, the lithium alloy with a three-dimensional structure can further reduce the internal resistance of the negative electrode and improve the rate performance of the battery.

[0043] In the present invention, in order to further inhibit lithium deposition at the interface between the lithium metal negative electrode and the diaphragm, the lithium content in the lithium metal composite negative electrode is regulated so that the lithium content in the lithium metal composite negative electrode gradually decreases along a first direction, and the first direction is the direction from the lithium metal layer to the polymer substrate layer; preferably, the lithium content in the composite layer accounts for 25%-75%, for example, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc., including but not limited to the content proportions listed above.

[0044] The smaller the resistance on the lithium metal negative electrode, the greater the probability of lithium deposition. For the negative electrode prepared by the traditional composite current collector, the concentration of lithium ions is high at the interface between the negative electrode surface and the diaphragm, and the deposition of lithium occurs preferentially at the interface between the electrode and the diaphragm, increasing the risk of battery short circuit. The present invention controls the distribution of lithium content in the composite layer in the above-mentioned lithium metal composite negative electrode, so that the lithium content of the lithium metal composite negative electrode gradually decreases along the direction of the lithium metal layer pointing to the polymer base layer, forming a conductive and lithium-philic double gradient (along the direction of the lithium metal layer pointing to the polymer base layer, the lithium-philicity gradually increases and the conductivity gradually decreases), the conductive gradient regulates the lithium nucleation trend of the lithium metal layer surface to be inferior to the bottom of the composite layer (at the interface with the polymer base layer), and the lithium-philic gradient regulates the lithium nucleation trend of the bottom of the composite layer to be better than the surface of the lithium metal layer. Under the action of the above-mentioned double gradient structure, the lithium nucleation trend of the bottom of the composite layer is much better than the surface of the lithium metal layer, thereby effectively inhibiting the lithium deposition at the interface between the negative electrode and the diaphragm, and greatly reducing the risk of short circuit of the lithium metal battery.

[0045] In the present invention, the first polymer can be selected from one or more of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polyamide, and polytetrafluoroethylene; the second polymer can be selected from one or more of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polyamide, and polytetrafluoroethylene; more preferably, the first polymer and the second polymer are the same polymer to improve the interface compatibility and adhesion between the polymer base layer and the composite layer.

[0046] In the present invention, the thickness of the first polymer substrate layer is preferably 4-8μm, for example 4μm, 5μm, 6μm, 7μm, 8μm, etc.; the thickness of the composite layer is preferably 0.5-5μm, for example 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc.; the thickness of the lithium metal layer is preferably 0.1-15μm, for example 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.; the thickness of the above layers includes but is not limited to the thicknesses listed above.

[0047] The present invention also provides a method for preparing the lithium metal composite negative electrode, comprising the following steps:

[0048] S1, providing material A, wherein material A comprises a first polymer, and material B comprises a second polymer and an M source;

[0049] S2, melting material A and material B to form melt A and melt B respectively, and stacking them in an AB or BAB arrangement, and forming a composite film layer by casting; the composite film layer includes an A film layer and a B film layer;

[0050] S3, covering the surface of the composite film layer where the B film layer is located with a lithium metal strip, and performing a hot rolling process to obtain the lithium metal composite negative electrode.

[0051] The present invention uses the method of melting, casting and rolling to form a lithium alloy with a three-dimensional structure and a conductive and lithium-philic dual gradient in situ by using the lithium metal element to diffuse into the composite layer under rolling conditions and alloy with the M source uniformly dispersed in the B film layer, thereby obtaining a lithium metal composite negative electrode with a polymer base layer, a composite layer and a lithium metal layer tightly combined. The above preparation method is simple to operate, low in cost, easy to realize industrial production, and has strong adaptability and universality; and the lithium metal composite negative electrode prepared by the above method has a stable structure and can effectively inhibit the formation of lithium dendrites, which is conducive to realizing a long-term stable cycle of a high-energy-density lithium metal battery at a high rate.

[0052] In some preferred embodiments, in step S1, the M source is M element and / or M oxide, wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn.

[0053] In some preferred embodiments, in step S1, the M source is in the form of one or more of nanoparticles, nanowires, and nanofibers; preferably, the particle size of the M source nanoparticles is 5-1000nm, and the cross-sectional diameter of the M source nanowires and M source nanofibers is 5-100nm, for example, silver nanowires with a cross-sectional diameter D50 of about 50nm.

[0054] In some preferred embodiments, in step S2, melt A and melt B are extruded through dies arranged in a certain arrangement so that the melts are stacked in an AB or BAB arrangement.

[0055] In some preferred embodiments, in step S2, the thickness of the A film layer is preferably 4-8μm, for example, 4μm, 5μm, 6μm, 7μm, 8μm, etc.; the thickness of the B film layer is preferably 0.5-5μm, for example, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., including but not limited to the layer thicknesses listed above.

[0056] In some preferred embodiments, in step S3, the thickness of the lithium metal strip is preferably 5-20 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., including but not limited to the layer thicknesses listed above.

[0057] In some preferred embodiments, in step S3, the lithium metal tape may be coated on the surface of the composite film layer where the B film layer is located by transfer printing.

[0058] In some preferred embodiments, in step S3, the rolling pressure is preferably 0.1-100 MPa, and the temperature is preferably 25-100°C.

[0059] The embodiments of the present invention also provide a lithium metal battery, comprising a lithium metal composite negative electrode prepared by the above preparation method.

[0060] In some preferred embodiments, the above-mentioned lithium metal composite negative electrode is used as a negative electrode plate to form a high-energy density lithium metal battery with a high-nickel ternary positive electrode, which exhibits excellent cycle stability during the cyclic charge and discharge process.

[0061] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0062] Example 1

[0063] This embodiment relates to the preparation of a lithium metal composite negative electrode, which is specifically as follows:

[0064] (1) providing a polymer PI material and a mixture of the polymer PI and silver nanowires (cross-sectional diameter D50 of 50 nm) uniformly mixed in a mass ratio of 15:85;

[0065] (2) The polymer PI material and the mixed material are respectively conveyed to the extrusion system, and after being melted, the melt is extruded from the upper, middle and lower dies, wherein the melt of the polymer PI material is extruded from the middle die, and the melt of the mixed material is extruded from the upper and lower dies, and a composite film is formed by casting with a PI layer in the middle having a thickness of 6 μm and a mixed layer having a thickness of 1.5 μm on the upper and lower sides;

[0066] (3) A lithium metal strip with a thickness of 15 μm is coated on both sides of the composite film obtained in step (2) and hot rolling is performed. The rolling pressure is set to 25 MPa and the temperature is set to 45°C. Under the action of hot rolling, the lithium metal and the Ag nanowires uniformly dispersed in the mixture layer form a composite layer with a thickness of 5.5 μm containing conductive, lithium-philic dual gradient and three-dimensional structure lithium-silver alloy (the thickness of the interactive contact layer formed by the lithium-silver alloy and the composite layer is 2 μm), and the thickness of the lithium metal layer is 10 μm, thereby obtaining a lithium metal composite negative electrode.

[0067] Example 2

[0068] This embodiment relates to the preparation of a lithium metal composite negative electrode, and the specific operations are as follows:

[0069] (1) providing a polymer PI material and a mixture of polymer PI and nano-SiO2 particles (particle size D50 is 180 nm) uniformly mixed in a mass ratio of 15:85;

[0070] (2) The polymer PI material and the mixed material are respectively conveyed to the extrusion system, and after being melted, the melt is extruded from the upper, middle and lower dies, wherein the melt of the polymer PI material is extruded from the middle die, and the melt of the mixed material is extruded from the upper and lower dies, and a composite film is formed by casting with a PI layer in the middle having a thickness of 6 μm and a mixed layer having a thickness of 1.5 μm on the upper and lower sides;

[0071] (3) A lithium metal strip with a thickness of 15 μm is coated on both sides of the composite film obtained in step (2) and hot rolling is performed. The rolling pressure is set to 25 MPa and the temperature is set to 45°C. Under the action of hot rolling, the lithium metal and the nano-SiO2 particles uniformly dispersed in the mixture layer form a composite layer with a thickness of 5.5 μm containing conductive, lithium-philic dual gradient and three-dimensional structure lithium-silicon alloy (the thickness of the interactive contact layer formed by the lithium-silicon alloy and the composite layer is 2 μm), and the thickness of the lithium metal layer is 10 μm, thereby obtaining a lithium metal composite negative electrode.

[0072] Example 3

[0073] This embodiment relates to the preparation of a lithium metal composite negative electrode, and the specific operations are as follows:

[0074] (1) providing a polymer PP material and a mixture of polymer PP and nano-SiO2 particles (particle size D50 is 180 nm) uniformly mixed in a mass ratio of 20:80;

[0075] (2) The polymer PP material and the mixed material are respectively conveyed to the extrusion system, and after being melted, the melt is extruded from the upper, middle and lower dies, wherein the melt of the polymer PP material is extruded from the middle die, and the melt of the mixed material is extruded from the upper and lower dies, and a composite film is formed by casting with a PP layer of 6 μm in the middle and a mixed layer of 1 μm in thickness on the upper and lower sides;

[0076] (3) A lithium metal strip with a thickness of 15 μm is coated on both sides of the composite film obtained in step (2) and hot rolling is performed. The rolling pressure is set to 20 MPa and the temperature is set to 45°C. Under the action of hot rolling, the lithium metal and the nano-SiO2 particles uniformly dispersed in the mixture layer form a composite layer with a thickness of 4.5 μm containing conductive, lithium-philic dual gradient and three-dimensional structure lithium-silicon alloy (the thickness of the interactive contact layer formed by the lithium-silicon alloy and the composite layer is 1.3 μm), and the thickness of the lithium metal layer is 11 μm, thereby obtaining a lithium metal composite negative electrode.

[0077] Comparative Example 1

[0078] This comparative example relates to the preparation of a lithium alloy-free polymer lithium metal composite negative electrode, which differs from Example 1 in that: it does not include the preparation of a mixture layer, and the other operations are the same; a lithium metal strip is directly coated on the PI layer, and a lithium alloy-free polymer lithium metal composite negative electrode is prepared by hot rolling, and the lithium metal composite negative electrode includes a polymer PI layer and a lithium metal layer stacked in sequence from the inside to the outside.

[0079] Comparative Example 2

[0080] This comparative example relates to the preparation of a lithium metal composite negative electrode, which differs from Example 1 in that: silver is directly magnetron sputtered onto the upper and lower sides of the polymer PI layer to prepare a composite film; the remaining operations are the same, and a lithium metal composite negative electrode containing a lithium-silver alloy is prepared, and the lithium metal composite negative electrode includes a polymer PI layer, a silver-lithium alloy layer (formed during hot rolling) and a lithium metal layer stacked in sequence from the inside to the outside.

[0081] Comparative Example 3

[0082] This comparative example relates to the preparation of a lithium metal composite negative electrode, which is different from Example 1 in that: copper is directly magnetron sputtered onto the upper and lower sides of the polymer PI layer to prepare a composite copper foil current collector; a lithium metal strip is rolled (the rolling pressure is set to 25 MPa, and the temperature is set to 45°C) onto the composite copper foil to obtain a lithium metal composite negative electrode, which includes a polymer PI layer, a copper metal layer and a lithium metal layer stacked in sequence from the inside to the outside.

[0083] Application and performance testing

[0084] (1) The peel strength of the lithium metal composite negative electrode prepared in the above embodiment and comparative example was tested, and the specific operation was as follows:

[0085] The lithium metal composite negative electrode prepared in each embodiment and comparative example was cut into 20×150 mm long strip samples. A tensile test was performed at room temperature with a rate set to 250 mm / min to record the peel strength between the polymer substrate layer and the metal layer.

[0086] The test results are shown in Table 1 below:

[0087] Table 1

[0088]

[0089]

[0090] It can be seen from Table 1 that compared with the conventional composite copper foil current collector, the peel strength between the metal layer and the polymer base layer in the lithium metal composite negative electrode prepared in Examples 1-3 is significantly improved, exceeding 300 times. It can be seen that the interface bonding force between the polymer layer and the metal layer in the lithium metal composite negative electrode provided by the present invention is strong and the structural stability is good.

[0091] It can be seen from Example 1 and Comparative Example 1 that introducing a composite layer comprising a polymer and a lithium alloy between the polymer base layer and the lithium metal layer can effectively improve the peel strength of the lithium metal composite negative electrode; while Comparative Example 2 directly introduces a silver metal layer on the polymer base layer by magnetron sputtering, and then alloys it with lithium metal to form a lithium-silver alloy to prepare a lithium metal composite negative electrode. Unlike Example 1, the lithium-silver alloy layer in the lithium metal composite negative electrode prepared in Comparative Example 2 only contains silver and lithium, but no polymer, and it is impossible to form an apparent three-dimensional structure with the lithium-silver alloy to improve the interfacial bonding force between the metal and the polymer. Therefore, the interface between the lithium alloy and the polymer base layer in the lithium metal composite negative electrode prepared in Comparative Example 2 still shows low adhesion, and the peel strength is much lower than that of the lithium metal composite negative electrode prepared in Example 1.

[0092] (2) The lithium metal composite negative electrodes prepared in the above embodiments and comparative examples were used as negative electrodes of lithium metal batteries to construct lithium metal batteries, and the electrical properties of each lithium metal battery were tested. The specific operation was as follows:

[0093] Construction of lithium metal battery: high nickel ternary positive electrode plate, separator, lithium metal composite negative electrode plate are stacked to obtain bare battery cell, positive and negative electrode tabs are welded, bare battery cell is installed in aluminum plastic film battery shell, liquid is injected, packaged, left to stand, formed, and capacity is divided to obtain lithium metal battery. Only the negative electrode plate is different in each lithium metal battery, and the others are the same.

[0094] The cycling performance test was carried out on lithium metal batteries constructed with different lithium metal battery negative electrodes: at room temperature, each lithium metal battery was charged to 4.25V at a constant current of 1C, then charged at a constant voltage of 4.25V until the current reached 0.05C cutoff, and then discharged to 2.8V at 0.33C, and the first discharge capacity was recorded. Then, the battery was charged and discharged in a cycle for 500, 1000, and 1750 cycles, and the discharge capacity of the 500th, 1000th, and 1750th cycles was recorded respectively. The capacity retention rate was calculated as (discharge capacity corresponding to the corresponding number of cycles / first discharge capacity) × 100%.

[0095] The above test results are shown in Table 2 below:

[0096] Table 2

[0097]

[0098] As shown in Table 2, the lithium metal battery prepared by using the lithium metal composite negative electrode prepared in Examples 1-3 of the present invention as the negative electrode sheet exhibits long cycle stability, and the capacity retention rate after 1000 cycles of charge and discharge is not less than 1000 cycles, and the capacity retention rate of the lithium metal battery is still above 85% after 1750 cycles of charge and discharge. However, the lithium metal battery constructed by the lithium metal composite negative electrode prepared in Comparative Examples 1-3 has only 500 cycles of charge and discharge, and the capacity has dropped to less than 30% of the initial discharge capacity.

[0099] It can be seen from this that the present invention can effectively improve the cycle life of lithium metal batteries by introducing a composite layer comprising a polymer and a lithium alloy between the polymer base layer and the lithium metal layer, so that the lithium metal battery has a high energy density and can be cycled stably and for a long time at a high rate.

[0100] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A lithium metal composite negative electrode, characterized in that: The lithium metal composite negative electrode comprises a polymer substrate layer, a composite layer and a lithium metal layer; The polymer base layer comprises a first polymer; The composite layer is disposed on at least one side of the polymer base layer along the thickness direction, and the composite layer comprises a second polymer and a lithium alloy, wherein the lithium alloy is LiM x , wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn, and x is 0.01-2; The lithium metal layer is arranged on a side of the composite layer away from the polymer substrate layer.

2. The lithium metal composite negative electrode according to claim 1, characterized in that In the composite layer, the lithium alloy has a three-dimensional network structure and is in interactive contact with the second polymer; The lithium content in the lithium metal composite negative electrode gradually decreases along a first direction, where the first direction is the direction from the lithium metal layer to the polymer substrate layer; The content of lithium in the composite layer is 25%-75%.

3. The lithium metal composite negative electrode according to claim 1, characterized in that The first polymer is selected from one or more of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polyamide, and polytetrafluoroethylene; The second polymer is selected from one or more of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polyamide, and polytetrafluoroethylene.

4. The lithium metal composite negative electrode according to claim 1 or 3, characterized in that: The first polymer and the second polymer are the same polymer.

5. The lithium metal composite negative electrode according to claim 1, characterized in that: The thickness of the first polymer substrate layer is 4-8 μm; The thickness of the composite layer is 0.5-5 μm; The thickness of the lithium metal layer is 0.1-15 μm.

6. A method for preparing a lithium metal composite negative electrode according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, providing material A, wherein material A comprises a first polymer, and material B comprises a second polymer and an M source; S2, melting material A and material B to form melt A and melt B respectively, and stacking them in an AB or BAB arrangement, and forming a composite film layer by casting; the composite film layer includes an A film layer and a B film layer; S3, covering the surface of the composite film layer where the B film layer is located with a lithium metal strip, and performing a roller pressing process to obtain the lithium metal composite negative electrode.

7. The preparation method according to claim 6, characterized in that: In step S1, the M source is M element and / or M oxide, wherein M is selected from one or more of Ag, Al, Ba, Bi, Ga, Ge, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, Mg, and Mn; The M source is in the form of one or more of nanoparticles, nanowires, and nanofibers; the particle size of the nanoparticles is 5-1000 nm, and the cross-sectional diameter of the nanowires and nanofibers is 5-100 nm; The mass proportion of the second polymer in the material B is 1%-30%.

8. The preparation method according to claim 6, characterized in that: In step S2, the thickness of the A film layer is 4-8 μm; The thickness of the B film layer is 0.5-5 μm.

9. The preparation method according to claim 6, characterized in that: In the step S3, the thickness of the lithium metal strip is 5-20 μm; The roller pressing has a pressure of 0.1-100 MPa and a temperature of 25-100°C.

10. A lithium metal battery comprising a negative electrode plate, characterized in that: The negative electrode plate is a lithium metal composite negative electrode as described in any one of claims 1 to 5, or a lithium metal composite negative electrode prepared by the preparation method as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Lithium ion capacitor and preparation method thereof

    CN110164701A

  • Polymer current collector, preparation method thereof, and related secondary battery, battery module, battery pack and device

    CN115176362A

  • Metal lithium polymer negative electrode capable of being used for secondary battery and preparation method of metal lithium polymer negative electrode

    CN115621419A

  • Metal lithium negative electrode, preparation method thereof and secondary battery

    CN116565136A

  • Modified lithium metal negative electrode and preparation method and application thereof

    CN116864622A